(3GdeMce hGdeMjW GdCYXes - (3Ydj Hf ESeGYjd, GdeYQha HGHf pSjnOg, CHh GdMSf , GdVQjQ GdCfOdSj,J (B458 (3g` s
(3ChdgG (B:s
(3ef HbjI MQa GdOGd hGdjGA hGdhGh (B: (3GdOhi GdeQVi bGd GddMjGfi OhGjI GddHf hGdgQjSI , hgh GdPi jZdX Ydjg EPG VQJg GdQjM ajUjQ eKd ZQa GdHjV s
(3BNQgG (B:s
(3ef HGH GdKdGKi Gddaja , GdgeRI hGdjGA hGdhGh , bhdg (B: (3ede jbhdhG (B: (3hCjJ ceG bGdhG (B: (3hYjJ hGeQCI hFjI MGaXI HjJgG eUdMI dg , hdGdg CYde hjJdhg MQa GdjGA hGdCda s
(3cJHJ GdUaMI GdChdi hGdCNjQI HNW eZGjQs
(3fSNI JGSYI LRA efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B211 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdYHGOdjI GdUGObjI (B- (3JhfS (B(2355) s
Keywords: (3GddZIs